2019
DOI: 10.1007/s11165-019-09895-9
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Encounters with Natural Selection During an Interactive Read Aloud

Abstract: Previous studies have shown that children as young as 5 years of age are able to form a basic understanding of evolution after listening to a storybook about natural selection. This study offers a semiotic exploration of children's meaning making during an interactive read aloud of the same storybook by investigating what children focus on and negotiate during the read aloud. Video data from eight interactive read aloud sessions (N = 24 children) were analysed using a multimodal approach and contrasted with se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…On one hand, this finding suggests that young children's reasoning about variation within a population remains an enormous challenge, a finding that resonates strongly with the literature (Emmons, Lees, and Kelemen 2017). However, discussions about variation frequently emerged during the interactive read-aloud that preceded the modelling activity (Frejd, 2019b), which indicates that it is not necessarily the actual concept of variation that is challenging for children, but rather the context or the mode of delivery that plays a significant role in children's meaning making (cf. Evans 1999).…”
Section: Utilising Interactional Resources To Demonstrate Evolutionarmentioning
confidence: 60%
See 4 more Smart Citations
“…On one hand, this finding suggests that young children's reasoning about variation within a population remains an enormous challenge, a finding that resonates strongly with the literature (Emmons, Lees, and Kelemen 2017). However, discussions about variation frequently emerged during the interactive read-aloud that preceded the modelling activity (Frejd, 2019b), which indicates that it is not necessarily the actual concept of variation that is challenging for children, but rather the context or the mode of delivery that plays a significant role in children's meaning making (cf. Evans 1999).…”
Section: Utilising Interactional Resources To Demonstrate Evolutionarmentioning
confidence: 60%
“…Emmons, Lees, and Kelemen 2017;Emmons, Smith, and Kelemen 2016;Kelemen et al 2014;Shtulman, Neal, and Lindquist 2016). A study by Frejd (2019b) has revealed that children are able to discuss and make meaning about evolutionary concepts from an interactive read-aloud. This exchange represents an unstructured and authentic classroom setting as opposed to a one-on-one read-aloud.…”
Section: Rationale and Research Aimmentioning
confidence: 99%
See 3 more Smart Citations